Multiple convex demarcation line for prediction of benign depressed gastric lesions in magnifying narrow-band imaging - Kanesaka, Takashi; Uedo, Noriya; Yao, Kenshi; Ezoe, Yasumasa; Doyama, Hisashi; Oda, Ichiro; Kaneko, Kazuhiro; Kawahara, Yoshiro; Yokoi, Chizu; Sugiura, Yasushi; Ishikawa, Hideki; Takeuchi, Yoji; Arao, Masamichi; Iwatsubo, Taro; Iwagami, Hiroyoshi; Matsuno, Kenji; Muto, Manabu; Saito, Yutaka; Tomita, Yasuhiko (Endoscopy International Open, 2018)
Background and study aims With magnifying narrow-band imaging (M-NBI) of the gastric mucosa, a characteristic demarcation line (DL) is occasionally found in non-cancerous depressed lesions. This DL forms multiple convex shapes along the edge of the epithelia of surrounding mucosa. We have termed this novel finding a multiple convex DL (MCDL). In this study, we clarified the prevalence of an MCDL in depressed gastric lesions detected in patients at high risk for gastric cancer and determined the diagnostic yield necessary to distinguish between cancer and non-cancer. Patients and methods This was a post hoc analysis of a multicenter prospective trial. In total, 362 small (≤ 10 mm) depressed lesions were detected in 1353 patients. Presence or absence of a DL in target lesions was evaluated on M-NBI images. The proportion of MCDLs among lesions with a DL was evaluated.Results Images of 347 lesions (39 cancerous and 308 non-cancerous) were evaluable. A DL was present in 252/347 lesions (73 %). When the cutoff value for the proportion of MCDLs needed to distinguish non-cancer from cancer was set at two-thirds, an MCDL was observed in 86/252 lesions (34 %). In 86 lesions with an MCDL, 83 (97 %) were non-cancerous. The sensitivity, specificity, positive predictive value, and negative predictive value of an MCDL for non-cancerous lesions were 38 %, 91 %, 97 %, and 19 %, respectively.Conclusions Presence of an MCDL had high specificity and positive predictive value for non-cancerous lesions. Evaluating the shape of the DL is useful for differentiation between cancer and non-cancerous lesions.